Internet and Islamic Learning Practices in Indonesia: Social Media, Religious Populism, and Religious Authority - Solahudin, Dindin (Religions, 2020)
Like in many other developing countries, Indonesia's population has been amongst the most enthusiastic uptakers' of the internet, especially of social media. Most Indonesians utilize the internet as an information source, including religious ones. Various groups and communities of Islamic studies have appeared on social media along with religious leaders who are also active on social media. Based on the various characteristics that have emerged, Islamic learning practices scattered across various social media platforms have increasingly illustrated the symptoms of religious populism. This is marked by the various socio-religious movements that have emerged from these practices. By using a digital religion perspective in order to observe Islamic learning practices on several social media platforms, this paper argues that social media has become a productive space for the development of religious populism in Indonesia. At first glance, religious populism on social media seems to challenge authoritative figures or religious institutions, but it can also be seen as a way for Islamic agents to convey Islamic teachings in a media-friendly culture.